2010
DOI: 10.1016/j.ejcts.2009.07.016
|View full text |Cite
|
Sign up to set email alerts
|

Acute respiratory dysfunction after surgery for acute type A aortic dissection

Abstract: Objective: Acute respiratory dysfunction (ARD) can occur after acute type A aortic dissection, but relatively little is known about ARD in such patients. This study aims to analyse the clinical impact of ARD after surgery for acute type A aortic dissection and to assess possible treatment options. Methods: We reviewed our institutional database to identify patients who underwent surgery for acute type A dissection between October 1994 and January 2008 (n = 276). Postoperative ARD was defined as oxygenation imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
32
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 15 publications
2
32
0
Order By: Relevance
“…The enrollment criteria were as follows: (I) patients who received repairment surgery for AADA; (II) patients with a persistent postoperative hypoxemia, which was defined as the blood gas exam showed that ratio of arterial partial pressure of oxygen (PaO 2 ) to fraction of inspired oxygen (FiO 2 ) was equal to or less than 200 mmHg (PaO 2 /FiO 2 ≤ 200) occurring within 24 h after ICU admission, lasting more than 2 h, and in the absence of other causes of pulmonary insufficiency such as cardiogenic pulmonary edema, pneumonia, pleural effusion, segmental atelectasis, pneumothorax, and pulmonary artery embolism [12]. The exclusion criteria were as follows: (I) patients who died within 24 h after surgery; (II) patients who developed severe postoperative complications such as: coma, cardiogenic shock, and gastrointestinal ischemia.…”
Section: Patientsmentioning
confidence: 99%
“…The enrollment criteria were as follows: (I) patients who received repairment surgery for AADA; (II) patients with a persistent postoperative hypoxemia, which was defined as the blood gas exam showed that ratio of arterial partial pressure of oxygen (PaO 2 ) to fraction of inspired oxygen (FiO 2 ) was equal to or less than 200 mmHg (PaO 2 /FiO 2 ≤ 200) occurring within 24 h after ICU admission, lasting more than 2 h, and in the absence of other causes of pulmonary insufficiency such as cardiogenic pulmonary edema, pneumonia, pleural effusion, segmental atelectasis, pneumothorax, and pulmonary artery embolism [12]. The exclusion criteria were as follows: (I) patients who died within 24 h after surgery; (II) patients who developed severe postoperative complications such as: coma, cardiogenic shock, and gastrointestinal ischemia.…”
Section: Patientsmentioning
confidence: 99%
“…We found that the patients with TAAD undergoing arch replacement were prone to a higher HAIs incidence rate (60%, 60 episodes/100 patients), the top three HAIs types were HAP (43%), VAP (27%) and BSIs (17%). The inflammation after TAAD, long duration of DHCA, and inadequate cooling of the lungs during surgery (20), intraoperative transfusion of banked blood (21) would increase the risk of pneumonia. Multivariate logistic regression analysis indicated that longer DHCA was an independent risk factor for postoperative HAIs.…”
Section: Discussionmentioning
confidence: 99%
“…Higher serum proinflammatory cytokine levels indicate higher morbidity in preoperative ALI in AAD, [4,37] whereas the primary biological function of serum IL-10 is to attenuate inflammatory responses and prevent impairment of endothelial dysfunction. [38] TXB 2 is the stable metabolite of TXA 2 , [39,40] a pro-inflammatory mediator.…”
Section: Discussionmentioning
confidence: 99%